IMPACT OF WEED HERBICIDES ON THE YIELD, GROWTH AND DEVELOPMENT OF MAIZE - Mustafoyeva Ozoda Ilashevna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The article presents data on the effect of the use of the herbicides Ximglifos and Ximstop against weeds in a corn field under typical gray soil conditions of the Tashkent region on the germination and development of corn. It was found that when Ximglifos was applied in the fall at a rate of 3.0 l/ha and Ximstop, 33% s.c. herbicide was applied simultaneously with sowing at a rate of 1.5 l/ha, it did not have a negative effect on the germination of corn, but rather increased germination.